Human Resource Management: The need for theory and diversity - Wolfgang Weber; Rüdiger Kabst (Management Revue, 2004)
Human Resource Management as an academic discipline needs to be theoretically grounded, i.e. it requires support through theories, theory-driven empirical research and critiques. In doing so, different theoretical perspectives are addressed suggesting a problem-orientated theory selection which leads inevitably to theoretical diversity.
Keywords: 650; Human Resource Management; systems theory; work and organizational psychology; behavioral approach; personnel economics; political economy; rational choice